2008
DOI: 10.1158/1078-0432.ccr-07-4358
|View full text |Cite
|
Sign up to set email alerts
|

ABTB/POZGene,NAC-1, a Tumor Recurrence–Associated Gene, as a Potential Target for Taxol Resistance in Ovarian Cancer

Abstract: Purpose: We previously determined that NAC-1, a transcription factor and member of the BTB/POZ gene family, is associated with recurrent ovarian carcinomas. In the current study, we investigated further the relationship between NAC-1expression and ovarian cancer. Experimental Design: NAC-1expression was assessed by immunohistochemistry, and clinical variables were collected by retrospective chart review. SiRNA system and NAC-1 gene transfection were used to asses NAC-1function inTaxol resistance in vivo. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 33 publications
4
44
0
Order By: Relevance
“…The mechanism underlying the association between NAC1 expression and shorter survival is not known; however, because mortality of patients with cervical carcinoma is directly related to the recurrence of disease after radiotherapy, it is conceivable that NAC1 expression may confer resistance to radiotherapy and/or enhance cell proliferation in radioresistant recurrent tumors. Recently, we reported that NAC1 was related to paclitaxel resistance in ovarian carcinomas [16,17]. The current findings of a positive relationship between NAC1 expression and adverse patient outcome may be explained by our previous findings.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…The mechanism underlying the association between NAC1 expression and shorter survival is not known; however, because mortality of patients with cervical carcinoma is directly related to the recurrence of disease after radiotherapy, it is conceivable that NAC1 expression may confer resistance to radiotherapy and/or enhance cell proliferation in radioresistant recurrent tumors. Recently, we reported that NAC1 was related to paclitaxel resistance in ovarian carcinomas [16,17]. The current findings of a positive relationship between NAC1 expression and adverse patient outcome may be explained by our previous findings.…”
Section: Discussionsupporting
confidence: 61%
“…The levels of NAC1 expression correlate with tumor recurrence in ovarian serous carcinomas, and intense NAC1 immunoreactivity in primary ovarian tumors predicts early recurrence [13,16]. In addition, NAC1 expression is related to taxane resistance in advancedstaged ovarian carcinomas [16,17]. Recently, we have reported that NAC1 expression is more common in cervical adenocarcinomas/adenosquamous carcinomas than in cervical squamous cell carcinomas and that NAC1 expression correlates with a worse prognosis in patients with squamous cell carcinomas of uterine cervix [15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…NAC1 is a transcription repressor that is involved in self renewal and the maintenance of pluripotency in embryonic stem cells (18). NAC1 is significantly overexpressed in several types of human carcinomas (17), where it plays a critical role in maintaining tumor cell proliferation and survival (17,(19)(20)(21). Recently, we showed that NAC1 is essential for the proliferation of normal cyclic endometrial glandular cells and is up-regulated by estrogen (22).…”
Section: Introductionmentioning
confidence: 99%